A formação inicial de pedagogos na perspectiva da Educação Matemática Inclusiva: A educação de surdos em foco - Silva, Virginia Eugenia da (2018)
This research is introduced on the Math Education context, more specifically in the teacher’s initial formation scene of the initial years proposing Math teaching to deaf children. Thus, the inclusive education has become an education paradigm. Living in a society of listeners, we realized that deaf individuals usually do not find opportunities to developing their cognitive potential. Therefore, the aim of this research is based on investigation of the understanding of the UEPB Pedagogy course students about teaching and learning process of Math with deaf students. So, we used the qualitative approach. The research carried out with thirteen students of the fifth period on the discipline of Special Education I of the State University of Paraíba, Campina Grande campus/PB. To this field rese arch we made a semi-structured interview. The theoretical basis used is based on the Education of Deaf, Initial Formation of Elementary School Teachers, the Math initial school grade and the Inclusive Math Education. The data analyzed obtained through manifestations of research participants, i.e., future pedagogues’; field diary and observations. To conduct data analysis, we used the methodological technique of Laurence Bardin, because the content analysis is a technique that provides to the researcher a variety of material and allowing a better understanding of the aim of the research. Thus, six categories emerged: The existence or not existence of a professional experience on the education area; The comprehension of deafness before established discussions in the discipline of the Special Education I; Realize deafness after academic experiences; The UEPB Pedagogy course in the formation of inclusive education to deaf individuals; Actions assumed by the school that help the inclusion of deaf students; The teaching-learning process on the Math Literacy. The first category shows if the participants have or do not have professional experience on the educational field. The second category talks about the deaf conceptions before the debates in the discipline of Special Education I. The third category discuss about the participants’ perceptions on deaf students after academic discussions and experiences. The fourth category discuss if the UEPB Pedagogy course is offering a formation that prepares the future pedagogues to work with deaf students. The fifth category debates about what actions the participants realize that the school should promote to deaf students inclusion. The sixth category talks about pedagogical practice that the teacher should adopt to teaching-learning process of the Mathematical Literacy contents to deaf students. The results shows that students that participated of the research start to realize after academic experiences the deaf individuals like efficient people, full of skills and potential. Noticed too that future teachers realized that it is necessary promotes the inclusion of deaf students, the school should be prepare with trained professionals to give support to needs of the students, moreover, emphasizes the needs of the usage of visual and manipulable pedagogical resources like abacus, golden material to promote a Math teaching of quality. In this regard, we concluded that the resources mentioned by the participants are also the essence in the teaching-learning process of listeners students.